2000
DOI: 10.1001/archfami.9.9.863
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Therapy for Herpes Zoster: Randomized, Controlled Clinical Trial of Valacyclovir and Famciclovir Therapy in Immunocompetent Patients 50 Years and Older

Abstract: Valacyclovir treatment is comparable to famciclovir treatment in speeding the resolution of zoster-associated pain and postherpetic neuralgia. Current wholesale prices indicate that valacyclovir is the more cost-effective treatment for herpes zoster ($83.90 vs $140.70 per course).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
1
12

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(90 citation statements)
references
References 18 publications
3
74
1
12
Order By: Relevance
“…However, our participants compared favourably with other study populations of patients with herpes zoster. 10,[33][34][35] Our results should thus be generalizable to patients seeking care for herpes zoster during the acute phase. Our data are also likely to present information bias such as learning effects because of repeated testing with the same instrument over time.…”
Section: Limitationsmentioning
confidence: 99%
“…However, our participants compared favourably with other study populations of patients with herpes zoster. 10,[33][34][35] Our results should thus be generalizable to patients seeking care for herpes zoster during the acute phase. Our data are also likely to present information bias such as learning effects because of repeated testing with the same instrument over time.…”
Section: Limitationsmentioning
confidence: 99%
“…A study highlighting the effi cacy of Zostavax revealed that cases of HZ were reduced by half in those who received the vaccine versus placebo. Participants who were vaccinated but still acquired HZ were 66% less likely to develop PHN than those given a placebo (18). Hence, the new HZ vaccine may reduce the incidence of HZ and its potential complications in patients with a heightened risk of developing the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The oral antiviral agent valacyclovir (Valtrex; GlaxoSmithKline, Tokyo, Japan) has been approved in Japan for several indications, including treatment for herpes zoster and genital herpes. We used the worldwide-approved valacyclovir dosage of 1 g, three times daily (Tyring et al, 2000) in our clinical trial.…”
Section: Vector and Valacyclovirmentioning
confidence: 99%